Vision and Audition Do Not Share Attentional Resources in Sustained Tasks - Arrighi, Roberto; Lunardi, Roy; Burr, David (Frontiers in Psychology, 2011)
Our perceptual capacities are limited by attentional resources. One important question is whether these resources are allocated separately to each sense or shared between them. We addressed this issue by asking subjects to perform a double task, either in the same modality or in different modalities (vision and audition). The primary task was a multiple object-tracking task (Pylyshyn & Storm, 1988), in which observers were required to track between 2-5 dots for 4 seconds. Concurrently, they were required to identify either which out of three gratings spaced over the interval differed in contrast or, in the auditory version of the same task, which tone differed in frequency relative to the two reference tones. The results show that while the concurrent visual contrast discrimination reduced tracking ability by about 0.7 d’, the concurrent auditory task had virtually no effect. This confirms previous reports that vision and audition use separate attentional resources, consistent with fMRI findings of attentional effects as early as V1 and A1. The results have clear implications for effective design of instrumentation and forms of audio-visual communication devices.